Synthesis of decyl mannoside: article - Shamsudin, Muhamad Baihakhi; Kamalul Aripin, Nurul Fadhilah (2018)
A new mixtures of mannose and decanol was synthesis. This synthesis main objective was to produce synthetic glycosides as one of the alternative for natural mannoside which consist of single alkyl chain with mannose head group. Three major procedures involved in the synthesis of decyl mannoside which are peracetylation, glycosylation and followed by deacetylation procedure. NMR analysis was used to determine the structure of the product and to analyze the product purity. The product which is decyl mannoside has purity of 67% due to some error might occur during synthesis procedure. Overall, the experiment was succesfull since the product was produced.